Aging in Persons with Rett Syndrome: An Updated Review - Meir Lotan; Joav Merrick; Isack Kandel; Mohammed Morad (The Scientific World Journal)
Rett syndrome (RS) is a neurological disease affecting mainly females, characterized by an arrest of brain development caused by an X-linked mutation. Rett syndrome is the first human disease found to be caused by defects in a protein involved in regulating gene expression through its interaction with methylated DNA. The disease has been traced to a defective gene called MECP2. The case stories presented here and recent findings show that females with RS are able to live into old age. Due to the observed longevity of individuals with RS, and the fact that individuals with RS present the therapist/physician with specific clinical challenges, it is suggested that proper, long-term, and individually tailored, intensive care should be provided at all ages in the hope to prevent or at least reduce the age-related deterioration that is typical of this population.